The Exploitation of the Elements of Nature in the Poetry Collection" (La Ghurbata) by Muhammad Omar Othman - مامۆستاى یاریدەدەر حەیدەر جەوهەر ئەحمەد (QALAAI ZANIST JOURNAL, 2021)
Nature has a prominent and influential role in human life. And has an important place in poets’ poems; it has become one of the sources inspired by the poet’s creative work. Among these poets is the poet Mohamed Omar Osman, a contemporary poet, who has a distinctive imprint in Kurdish poetry because of his creative presentation and his creative abilities in his poetic productions. This study, entitled "The Exploitation of the Elements of Nature in the Poetry Collection" (La Ghurbata) by Muhammad Omar Othman, is an attempt to explain the location of the elements of nature in the world of his poetry, because the elements of nature took great place in the texts of the poet. The study consists of an introduction, two axes and a conclusion, as follows: The first axis dealt with the concept of nature, in terms of significance, terminology and definition. This was covered by the opinion of specialists, as well as the role of nature in literary space, in an attempt to demonstrate the influence of literature on the poet and his literary works. The second axis was devoted to the nature of rigid and dynamic nature of the poet’s output; with a statement of the poet’s efforts in how to employ these natural elements in his poetry; in a painting filled with beautiful pictures and careful and deep consideration. In the end, the research reached a number of results with the sources mentioned at the end .